Amorphous Ternary Ceramics Instability Below 450°C: Nano‐Scale Arguments from the Lattice Compatibility Theory (LCT). Issue 3 (21st February 2013) - Boubaker, Karem; Amlouk, Mosbah
<x xml:space="preserve">Abstract</x> In this paper, we present some elements of the lattice compatibility theory (LCT) as plausible explanations to the problem of instability of some ternary ceramics under some circumstances. Particular attention is paid to ceramics nano‐scale patterns.